INDUSTRI RUMAH TANGGA PENGAWETAN IKAN DI DESA ERETAN KECAMATAN KANDANGHAUR KABUPATEN INDRAMAYU - Ken Suratiyah; Nurhaesih Nurhaesih (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2000)
This research use descriptive analities method, suppose to understanding: earning profit, women time allocation, feasibility study and contribution of fish preservation home industry to total household income.The reason of choosing fish preservation home industry are: less capital, work location and labor that handle this industry have positive impact especially for house wife and children, and they can use their leisure time optimally.The contribution of fish preservation home industry to total fisher household income is about 78% and influence fulfilling family necessity.The increasing of income influence fisher family prosperity (according to Sayogyo, KFM and BPS Standards) before carry on fish preservation home industry shows that they have been prosperous. But after carry on this home industry their prosperity increase too, this influence unbalance income that not spread